A useful inequality for quaternion linear canonical transform - Bahri, Mawardi (KOMUNITAS Analisis Matematika INDONESIA, 2022)
In this work, we first introduce the quaternion Fourier transform. We explore its relation to the quaternion linear Fourier transform and utilize this fact to extend an inequality for the quaternion Fourier transform in the framework of the quaternion linear canonical transform.